(untitled) (The Batuk, 2021)
This paper aims to examine the understanding of organizational politics and its impact on the job performance of Nepal’s civil service employees. The research design adopted in this study consists of a descriptive and causal-comparative research design. Based on a multi-stage random sampling, 250 civil servants in five ministries of the Nepal Government were selected as sample. The response rate was 76.40 percent. The findings of this research indicate that strong organizational politics exist at government offices. Mainly, over politics exist in the case of pay and promotion policies. Likewise, going along to get ahead and general political behavior are also common at these offices. The job performance level, however, was found at an average level. The inferential results indicate that there is a significant negative impact of organizational politics (in terms of going along to get ahead, pay and promotion policies, and general political behavior) on the job performance of employees. Therefore, leaders and administrators of ministries and other government offices need to keep an eye open in such realities and try to reduce unnecessary politics at workplaces so that the civil servants can focus on delivering effective services to the general public.